2021
DOI: 10.1109/taffc.2019.2901456
|View full text |Cite
|
Sign up to set email alerts
|

An EEG-Based Brain Computer Interface for Emotion Recognition and Its Application in Patients with Disorder of Consciousness

Abstract: Recognizing human emotions based on electroencephalogram (EEG) signals has received a great deal of attentions. Most of the existing studies focused on offline analysis, and real-time emotion recognition using a brain computer interface (BCI) approach remains to be further investigated. In this paper, we proposed an EEG-based BCI system for emotion recognition. Specifically, two classes of video clips that represented positive and negative emotions were presented to the subjects one by one, while the EEG data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(63 citation statements)
references
References 55 publications
(76 reference statements)
0
63
0
Order By: Relevance
“…Multisensory channel integration to induce subjects’ emotions, especially video material that involves emotion recognition evoked by visual and auditory stimuli, will be a future trend. For audio-visual emotion recognition, a real-time BCI system to identify the emotions of patients with consciousness disorders was proposed [ 10 ]. Specifically, two classes of video clips were used to induce positive and negative emotions sequentially in the subjects, and the EEG data were collected and processed simultaneously.…”
Section: Heterogeneous Sensory Stimulimentioning
confidence: 99%
See 2 more Smart Citations
“…Multisensory channel integration to induce subjects’ emotions, especially video material that involves emotion recognition evoked by visual and auditory stimuli, will be a future trend. For audio-visual emotion recognition, a real-time BCI system to identify the emotions of patients with consciousness disorders was proposed [ 10 ]. Specifically, two classes of video clips were used to induce positive and negative emotions sequentially in the subjects, and the EEG data were collected and processed simultaneously.…”
Section: Heterogeneous Sensory Stimulimentioning
confidence: 99%
“…The existing research on emotion recognition mainly involves offline analysis. For the first time, Huang et al [ 10 ] applied an aBCI online system to the emotion recognition of patients with disorders of consciousness. Using this system, they were able to successfully induce and detect the emotional characteristics of some patients with consciousness disorders in real time.…”
Section: Open Challenges and Opportunitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, studies using physiological signals to recognize emotional states such as electroencephalogram (EEG)-based brain-computer interface systems (BCI) are also providing interesting results, and there is promise for use in a number of real-world applications. Huang et al (2019) showed participants video clips with negative and positive valence while recording EEG. The EEG-based BCI system successfully induced and recognized positive and negative emotional states in patients with Disorders of Consciousness.…”
Section: Related Workmentioning
confidence: 99%
“…Pan et al [25] used the emotion-related common spatial pattern and differential entropy features of five frequency bands in their research. To acquire the time-varying characteristics reflected by EEG frequency data, the short-time Fourier transform was used to analyze EEG signals [26,27]. As EEG signals are time-varying, researchers proposed new methods to obtain additional information by combining time and frequency-domain features.…”
Section: Introductionmentioning
confidence: 99%